Joseph Penso de Vega La creación de un perfil cultural y literario entre Ámsterdam y Livorno - Pancorbo, Fernando José (Storia dell'Ebraismo in Italia. Studi e testi, 2019)
This book is the completest work about life and works of Joseph Penso de Vega, the most prominent author of the Jewish Community of Amsterdam in the XVIIth century. This volume presents a very interdisciplinary study, because of the frequent contacts that the writer had among diasporas and the cultural relationship with Christians and laics. That meant a very intense cultural and literary exchange that Penso knew to represent it in his texts. In this sense, this study offers a very exact portrait -never made before-, not only about his cultural production but also about him as nexus between diasporas concerning religious aspects, History of culture and history of ideas, aspects ignored before but basics to understand his works.